TRANSFORMATIONAL LEADERSHIP IN ISLAMIC EDUCATION MANAGEMENT IN THE DIGITAL ERA: STRATEGIES TO IMPROVE INNOVATION, QUALITY, AND COMPETITIVENESS OF EDUCATIONAL INSTITUTIONS - Ellisa Nailizzulfa; Sukarman Sukarman; Muhammad Khoiruddin (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2026)
This research aims to analyze the role of transformational leadership in Islamic education management in the digital era and identify strategies that can be applied to improve the innovation, quality, and competitiveness of educational institutions. The research uses a qualitative approach with the library research method. Data sources were obtained from books, scientific journal articles, proceedings, and relevant academic documents regarding transformational leadership, Islamic education management, and digital transformation. Data collection techniques are carried out through documentation and literature review, while data analysis uses the Miles, Huberman, and Saldaña interactive model which includes data reduction, data presentation, and conclusion drawn. The results of the study show that transformational leadership plays an important role in encouraging educational innovation through the digitalization of learning, strengthening teachers' digital competencies, and developing an adaptive organizational culture. In addition, the application of inspirational motivation, intellectual stimulation, individual attention, and exemplary values based on Islamic values has been proven to be able to improve the quality of educational services and strengthen the competitiveness of Islamic educational institutions in the digital era. This study concludes that the integration of transformational leadership with Islamic values and the use of digital technology is an effective strategy to realize innovative, quality, and sustainable Islamic educational institutions.